Sistem Pakar Diagnosis Kerusakan Mobil MVP Berbasis Internet - Sunarti , ST, M. Kom; Wilda Susanti; Monang Adi Candra (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Car transport is a very valuable tool for people to travel from one place to another. Frequent carusers difficulties when their car was damaged, because lack of knowledge of car users inanalyzing troubleshooting the car in general and there has not been available a proper system model inproviding solutions to the damage of the car. Expert systems is a solution to help car users in givingknowledge to the car user in analyzing the damage of the car. Method of backward chaining and Methodof depth first search (DFS) is a method used to search the damage to the car.The process of tracing the damage done to the car by using a rule-based. Designing aknowledge base (knowledge base) is done by making a tree consisting of inference components, type ofdamage and damage characteristic that describes the problem until they reached the conclusion andsolutions the car problems these are stored into the Database Management System (DBMS). The next willbe determined the weight of the response of each problem so that can be formulated the value of thepercentage of damage to the car.Expert system is expected to perform toubleshooting process (problem solving) cars and canprovide solutions like an expert and can be accessed via the internet.Keyword : Car, Expert System, Backward Chaining, DFS, Database Management System